Дифузні процеси в лексиці української мови (на прикладі варваризмів мас-медійних текстів) - Навальна, Марина; Navalna, Maryna (Східноєвропейський національний університет імені Лесі Українки, 2015)
У статті проаналізовано слова та словосполуки, запозичені з інших мов, що активно вживаються в мові сучасної української періодики в різному написанні – латиницею та кирилицею, згрупувано їх за способами написання, досліджено тематичну спрямованість запозичень у газетному мовленні, визначено їхню стилістичну роль. In the article the words and phrases, borrowed from other languages, are actively used in the modern Ukrainian language periodicals in a different spelling - Roman and Cyrillic, they were grouped by way of writing, analyzed the thematic unity of borrowing in the newspaper, determined their stylistic role. Characterized borrowing mainly of Anglo-American origin are caused by extralinguistic factors: the democratic processes in the society, cooperation with foreign countries, the lack of censorship and the like. There are several groups of foreign words and phrases: 1) those that are reproduced in Roman; 2) those that are written in Roman, and Cyrillic; 3) transcribed units. It was traced and described the use of neologisms in the language of periodicals, in particular, in the composition of names.
Diffusion Processes in the Vocabulary of the Ukrainian Language (for Example, Barbarisms of Mass Media Texts)
Keywords: варваризми; стилістична роль; мова української періодики; тематична спрямованість; дифузність лексики; barbarisms; stylistic role; language of Ukrainian periodicals; thematic focus; vocabulary diffusivity